To solve for m, we can start by distributing 0.5 to both terms within the parentheses on the left side of the equation:
0.5m + 2 = 3m - 3
Next, we can combine like terms by subtracting 0.5m from both sides of the equation:
2 = 2.5m - 3
Then, we can add 3 to both sides of the equation:
5 = 2.5m
Finally, we can divide both sides of the equation by 2.5 to solve for m:
m = 5/2.5
m = 2
Therefore, the solution to the equation is m = 2. So the correct answer is 2.
0.5(m + 4) = 3(m – 1)
(1 point)
Responses
–2
2
no solution
identity
1 answer